2007
DOI: 10.1038/sj.onc.1210774
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional repressor NIPP1 is an essential player in EZH2-mediated gene silencing

Abstract: EZH2 is a Polycomb group (PcG) protein that promotes the late-stage development of cancer by silencing a specific set of genes, at least in part through trimethylation of associated histone H3 on Lys 27 (H3K27). Nuclear inhibitor of protein phosphatase-1 (NIPP1) is a ubiquitously expressed transcriptional repressor that has binding sites for the EZH2 interactor EED. Here, we examine the contribution of NIPP1 to EZH2-mediated gene silencing. Studies on NIPP1-deficient cells disclose a widespread and essential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 48 publications
4
87
0
Order By: Relevance
“…Although EZH2 is commonly known for its role in gene silencing through generation of H3K27me3, several works reveal that EZH2 also positively regulates gene expression through both indirect effects and effects that are independent of its catalytic activity (33)(34)(35). Our study also identified a subset of olaparib-affected genes of LCL cells that are included in the group of targets positively regulated by EZH2 in PC3 cells, supporting the additional role for EZH2 itself as a positive regulator of gene expression.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Although EZH2 is commonly known for its role in gene silencing through generation of H3K27me3, several works reveal that EZH2 also positively regulates gene expression through both indirect effects and effects that are independent of its catalytic activity (33)(34)(35). Our study also identified a subset of olaparib-affected genes of LCL cells that are included in the group of targets positively regulated by EZH2 in PC3 cells, supporting the additional role for EZH2 itself as a positive regulator of gene expression.…”
Section: Discussionsupporting
confidence: 49%
“…GSEA identified olaparib-affected genes enriched in the EZH2 target gene data set. In the work by Nuytten et al, depletion of EZH2 resulted in both activation and repression of a subset of genes (35). Thus, in cells depleted of EZH2, genes that were upregulated represent genes for which EZH2 acts as a repressor, while genes that were downregulated represent genes for which EZH2 functions, likely indirectly, as a transcriptional activator.…”
Section: Lcl Cells Tolerate Parp Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…involved in gene silencing, at least in part through trimethylating histone 3 Lys 27. It also interacts with DNA methyltransferases and it is necessary for the methylation of target DNA (Vire et al, 2006;Nuytten et al, 2008). Through these interactions, the downregulation of the gene coding for Ser/Thr protein phosphatase in the F 1 Zn þ and F 1 Zn À daphnids could be a reason for their reduced global DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Our work extends these previous findings by providing a mechanism demonstrating that LMP1, through PARP1, affects EZH2 and H3K27me3. Since EZH2 also promotes gene expression by mechanisms that are independent of its catalytic activity (50,51), EBV may exploit multiple regulatory functions of EZH2, some of which directly alter host transcription without associated epigenetic modifications. Therefore, this work defines a mechanism for LMP1-mediated host gene expression regulation via PARP1-dependent inhibition of H3K27me3 production and possibly suppression of EZH2 transactivation.…”
Section: Discussionmentioning
confidence: 99%